Are associations between home environment and preschool children's sedentary time influenced by parental educational level in a cross-sectional survey? - Elviira Lehto; Reetta Lehto; Carola Ray; Riikka Pajulahti; Nina Sajaniemi; Maijaliisa Erkkola; Eva Roos (BMC, 2021)
Abstract Background Childhood obesity is a major public health concern, especially in low socioeconomic groups. Sedentary time (SED) is an important predictor of obesity. To be able to diminish SED it is important to find modifiable predictors of sedentary behavior. The home environment associated with children's SED may vary by parental socioeconomic status. This study aims to clarify the association between parental educational level (PEL) and the home environment of 3-6-year-old children, and to examine how home environment associates with children's SED, and whether PEL modifies these associations. Methods A cross-sectional Increased health and wellbeing in preschools (DAGIS) study was conducted in 2015-2016 in Finland. The parents (n = 809) filled in questionnaires assessing PEL, and the home physical and social environment related to children's SED. Children's SED was measured with accelerometers, which the children (n = 745) wore for 1 week. Results High PEL was associated with a home environment restraining sedentary behaviour compared with low PEL. Stricter descriptive norms about screen time, considering it important to limit the child's screen time, and satisfaction about the child's screen time associated with children's lower SED. The association with parental psychological control and SED was influenced by PEL. In the PEL stratified analyses, however, the associations between psychological control and SED did not reach statistical significance. Conclusions Future interventions aiming to decrease SED should pay attention to relevant factors in children's sedentary behaviour home environment. It is important to acknowledge the possible PEL differences in these factors.